2017
DOI: 10.1039/c7ra07195g
|View full text |Cite
|
Sign up to set email alerts
|

Study on the preparation and performance of low gas permeability trifluoropropyl phenyl silicone rubber

Abstract: Low gas permeability coating can prevent oxygen and sulphur vapour from permeating into silicone rubber and protect electronic components, chips, electrodes, medicines, etc. from oxidation and sulfuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Therefore, acceptable sulfurization resistance could be obtained. Notably, after the LEDs were exposed to sulfur gas for 24 h, those encapsulated with samples 3 and 4 exhibited higher flux retention than that encapsulated with only trifluoropropyl phenyl silicone rubber or even with an additional protective polysilazane top layer [21]. The much longer duration time of approximately 240 h provided strong evidence of the durability of the present siloxane-modified epoxy recipe.…”
Section: Sulfurization Resistance Of the Transparent Siloxane-modifiementioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, acceptable sulfurization resistance could be obtained. Notably, after the LEDs were exposed to sulfur gas for 24 h, those encapsulated with samples 3 and 4 exhibited higher flux retention than that encapsulated with only trifluoropropyl phenyl silicone rubber or even with an additional protective polysilazane top layer [21]. The much longer duration time of approximately 240 h provided strong evidence of the durability of the present siloxane-modified epoxy recipe.…”
Section: Sulfurization Resistance Of the Transparent Siloxane-modifiementioning
confidence: 82%
“…The second option is to employ vapor deposition or coat a dense inorganic or organic material (e.g., SiOx, Al 2 O 3 , or organic polysilazane) onto the surface of the polymer matrix. However, this approach requires special facilities (e.g., CVD and vacuum conditions) and complicated processes [21][22][23].…”
mentioning
confidence: 99%
“…Upon infusion, the lubricant immediately spread across the samples and the surfaces regained transparency. This change was induced by the similar refractive indices of the PVDF-PMMA blend and PTFS oil1.44 and 1.43, respectively. Transparency indicated that a continuous layer had been formed between the substrate and the lubricant and that all of the air gaps present on the surface had been filled.…”
Section: Results and Discussionmentioning
confidence: 99%
“…One possible approach is use of fluoroelastomer that has low air permeability and high-temperature resistance [48]. Mixing nanoparticles in polymer materials [49] or surface coating with low permeability materials [50] could be an other alternative.…”
Section: Discussionmentioning
confidence: 99%